Darwinians, Communitarians, and Missionaries: The Role of Founder Identity in Entrepreneurship - Fauchart, Emmanuelle; Gruber, Marc (Academy of Management Journal, 2011)
Drawing on social identity theory, we explore the identities, behaviors, and actions of 49 firm founders in the sports-related equipment industry. Our analysis suggests the existence of three pure types of founder identities and shows how these identities systematically shape key decisions in the creation of new firms, thereby “imprinting” the start-ups with the founders' distinct self-concepts. We synthesize our findings in a typology that sheds light on the heterogeneous meanings that founders associate with new firm creation and that improves understanding as to why fundamental differences in firm creation processes and outcomes exist.